Identity of Speech Community in Biak Numfor Papua: Anthropolinguistic Study Perspective - Hugo Warami (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
Language and cultural richness of Biak Numfor in Papua is part of a national identity characterized by